(untitled) (GEOmedia, 2022)
QGIS is the leading free and open source desktop GIS. It is also a complete ecosystem, that allows to build complete workflows, from field data collection to publication on the web. Central to it are QGIS projects, that define data sources, projections, styling and integration, and are reused from mobile to the web without a need to reconfigure them. We describe the main solutions available for data collection and seamless publication over the web: MerginMaps, Qfield, Lizmap, with an example form a water resources project in Gambia.